SOS/DBD-based solid state switching for ultra-high-power short pulse generation; Conference Record of the Twenty-Fifth International Power Modulator Symposium and 2002 High-Voltage Workshop, Hollywood, CA, june 30 - july 3, 2002 - Rukin S. N.; Alichkin E. A.; Lyubutin S. K.; Mesyats G. A. Gennady Andreyevich; Ponomarev A. V.; Slovikovsky B. G.; Timoshenkov S. P. (2002, 2002)
В фонде НТБ ТПУ отсутствует